Association between serum copper and blood glucose: a mediation analysis of inflammation indicators in the NHANES (2011–2016) - Cheng, Zijing; Kong, Yuzhe; Yang, Wenqi; Xu, Haitao; Tang, Decheng; Zuo, Yu (Frontiers in Public Health, 2024)
The rising prevalence of diabetes underscores the need for identifying effective prevention strategies. Recent research suggests environmental factors, particularly heavy metals like copper, significantly influence health outcomes, including diabetes, through mechanisms involving inflammation and oxidative stress.This study aims to explore how serum copper levels affect blood glucose, employing NHANES data from 2011-2016, to provide insights into environmental health's role in diabetes prevention and management.The study analyzed data from 2318 NHANES participants across three cycles (2011)(2012)(2013)(2014)(2015)(2016), focusing on those with available data on serum copper, inflammatory markers, and blood glucose levels. We utilized principal component analysis for selecting inflammatory markers, mediation analysis to examine direct and indirect effects, multiple linear regression for assessing relationships between markers and glucose levels, and weighted quantile sum regression for evaluating individual and collective marker effects, adjusting for demographic variables and serum copper.Results: Participants averaged 42.70 years of age, with a near-even split between genders. Average serum copper was 119.50 µg/dL, white blood cell count 6.82 x109/L, and fasting blood glucose 107.10 mg/dL. Analyses identified significant mediation by inflammatory markers (especially white blood cells: 39.78%) in the copper-blood glucose relationship. Regression analyses highlighted a positive correlation between white blood cells (estimate: 1.077, 95% CI: 0.432 to 2.490, p = 0.013) and copper levels and a negative correlation for monocyte percentage (estimate: -1.573, 95% CI: 0.520 to -3.025, p = 0.003). Neutrophil percentage was notably influential in glucose levels. Sensitive analyses confirmed the study's findings.Serum copper levels significantly impact blood glucose through inflammatory marker mediation, highlighting the importance of considering environmental factors in diabetes management and prevention. These findings advocate for public health interventions and policies targeting environmental monitoring and heavy metal exposure reduction, emphasizing the potential of environmental health measures in combating diabetes incidence.